Study on e-cigarettes and pregnancy (STEP): results of a mixed methods study on risk perception of E-Cigarette use during pregnancy = Studie zu E-Zigaretten und Schwangerschaft (STEP) : Ergebnisse aus einer Mixed-Methods-Studie zur Risikowahrnehmung der E-Zigaretten-Nutzung in der Schwangerschaft - Schilling, Laura; Spallek, Jacob; Maul, Holger; Schneider, Sven (Geburtshilfe und Frauenheilkunde, 2021)
Introduction: E-cigarette use during pregnancy is a risk factor for maternal and fetal health. Early studies on animals showed that in utero exposure to e-cigarettes can have negative health outcomes for the fetus. There has been only limited research into the risk perceptions of e-cigarette use during pregnancy. This study was conducted to comprehensively characterize the constructs of risk perceptions with regard to e-cigarette use during pregnancy using an Integrated Health Belief Model (IHBM). Methods: Our STudy on E-cigarettes and Pregnancy (STEP) used a mixed methods approach, with the study divided into an initial qualitative part and a quantitative part. A netnographic approach was used for the first part, which consisted of the analysis of 1552 posts from 25 German-language online discussion threads on e-cigarette use during pregnancy. Using these qualitative results, a quantitative questionnaire was developed to explore risk perception constructs about e-cigarette use during pregnancy. This questionnaire was subsequently administered to pregnant women (n = 575) in one hospital in Hamburg, Germany. Descriptive and bivariate analysis was used to examine differences in risk perception according to participantsʼ tobacco and e-cigarette user status before and during pregnancy. While the study design, methods and sample have been extensively described in our recently published study protocol in the January 2020 issue of Geburtshilfe und Frauenheilkunde, this paper is devoted to a presentation of the results of our mixed methods study. Results: Themes related to perceived threats identified in the qualitative study part were nicotine-related health risks and potential health risks of additional ingredients. Perceived benefits were possibility and facilitation of smoking cessation and a presumed potential to reduce harm. The subsequent quantitative part showed that nearly all participants (99.3%) perceived e-cigarettes which contained nicotine as constituting a threat to the health of the unborn child. The most commonly perceived barrier was health-related (96.6%), while the most commonly perceived benefit was a reduction in the amount of tobacco cigarettes consumed (31.8%). We found that particularly perceived benefits varied depending on the participantʼs tobacco and e-cigarette user status. Conclusion: When considering future prevention strategies, the potential health risks and disputed effectiveness of e-cigarettes as a tool for smoking cessation need to be taken into account and critically discussed.